The t(14;18) translocation is absent from endothelial and follicular dendritic cells of follicular lymphoma (FL) and shows heterogeneous presence in preserved FL mantle zones - Perikles Kosmidis; Barbara Mankel; Falko Fend; Patrick Adam (BMC, 2018)
Abstract Background The translocation t(14;18)(q32;q21) is the genetic hallmark of follicular lymphoma (FL) and can be observed in 85-90% of cases. Whether the translocation is restricted to cells with germinal center B-cell phenotype or can be observed in other cell types of the microenvironment remains debated. Of interest, cases of associated histiocytic and dendritic cell sarcomas arising in the background of FL have been shown to be clonally related and carry the t(14;18), suggesting a "transdifferentiation" of the malignant FL clone into a neoplasm of a different hematopoietic lineage. Methods We analyzed the presence of the t(14;18)(q32;q21) as a surrogate marker of the malignant clone in cells of the FL microenvironment using combined fluorescence immunophenotyping and interphase cytogenetics targeting the BCL2 gene locus. In addition to non-lymphoid cells in FL, we analysed FL with preserved IgD+ mantle zones and cases of in situ follicular neoplasia (ISFN) to investigate whether cells of non-germinal center B-cell phenotype are part of the malignant clone. Results Six (40%) of 15 manifest FL cases with preserved IgD+ mantle zones did not harbour the t(14;18)(q32;q21) translocation. In all t(14;18) + FL cases, follicular dendritic cells and endothelial cells lacked the t(14;18) translocation. 2/9 FL revealed t(14;18)- IgD+ mantle zone B-cells. In the seven ISFN cases, the t(14;18) translocation was strictly confined to germinal center cells. Conclusions The t(14;18) translocation in follicular lymphoma is limited to B-cells. The origin of IgD+ mantle cells is heterogeneous, in the majority of cases belonging to the neoplastic clone, whereas a minority of cases of manifest FL show nonneoplastic mantle zones, similar to ISFN.